Rozwiązane

Rozwiąż równania:

A) x+41=(2x+13)-(x-28)

B) 3(x-1)+2=8x-3

C) x/3-x/6=4+x/2​



Odpowiedź :

Odpowiedź:

A) x + 41 = 2x + 13 - x + 28

x + 41 = x + 41

x - x = 41 - 41

0 = 0

B) 3x - 3 + 2 = 8x - 3

3x - 1 = 8x - 3

3x - 8x = -3 + 1

-5x = -2 (nie wiem dlaczego tam wyszło więc może być ten punkt źle)

C) x/3 - x/6 = 4 + x/2

x/3 - x/6 - x/2 = 4

2x/6 - x/6 - 3x/6 = 4

-2x/6 = 4

x = -12

ponieważ -2 * -12 : 6 = 24 : 6 = 4

Szczegółowe wyjaśnienie:

nie wiem czy to jest dobrze więc przepraszam jak jest źle